Exposure to pornography in a young boy: Diagnosis and management - Prahbhjot Malhi; Bhavneet Bharti; Dileep Satya (Wolters Kluwer Medknow Publications, 2021)
Background: Child sexual abuse is highly prevalent in India, both among boys and girls; however, few studies have studied sexual abuse of male children. The present case report highlights the challenges of diagnosis and management of a young boy who presented with marked hyperactivity and sexual acting out behaviors subsequent to his repeated exposure to pornography. Clinical Description: H, a 5-year-old boy, presented with a 2 month history of hyperactivity, poor concentration, inappropriate touching, and self-stimulation. H also displayed sexual knowledge beyond that of what would be expected of his age and developmental level. The Child Sexual Behavior Inventory was administered that showed an unusually high score on the (sexual abuse specific items, sexual behaviors that are atypical for child's age and gender). Management and Outcome: The use of therapeutic interventions such as building a therapeutic relationship, environmental change, family counseling, and nondirective play therapy helped in remitting most of the child's behavioral difficulties. Conclusions: Parents need to be active participants in the digital lives of their children and exercise controls on what they view online. Since pediatricians are often the first points of contact for a child with aberrant behaviors, they need to be aware of the law on the protection of children against sexual offenses and the range of types of sexual offenses against children.